Ferroptosis at the intersection of osteoarthritis and bone metabolism: mechanistic links and therapeutic prospects - Xiao, Jing; Zhu, Yan; Chen, Jingjing; Hong, Yujie; Cao, Yang (Frontiers in Cell and Developmental Biology, 2025)
Osteoarthritis (OA) is a highly prevalent and debilitating degenerative joint disorder worldwide, characterized by complex pathogenesis and a lack of effective disease-modifying therapies. The traditional perspective has evolved from a simplistic “cartilage wear” model to a “whole-joint” pathology encompassing synovitis, aberrant subchondral bone remodeling, and chondrocyte death. In recent years, ferroptosis has emerged as a critical player in OA pathogenesis because of its unique regulatory mechanisms. Accumulating evidence indicates that ferroptosis contributes to OA progression through core processes, including intracellular iron overload, antioxidant system collapse, and excessive lipid peroxidation. These events not only directly trigger chondrocyte death and extracellular matrix degradation but also exacerbate bone metabolic imbalance through intricate signaling networks. Notably, the proposed “iron overload–inflammation–bone metabolism” vicious cycle underscores the central role of ferroptosis in linking cartilage degeneration to abnormal subchondral bone remodeling, providing a novel conceptual framework for understanding the “cartilage–bone” axis in OA. This review systematically outlines the molecular mechanisms of ferroptosis and its functional roles in OA chondrocytes and bone metabolism, emphasizing the pathological implications of this vicious cycle. We further discuss preclinical advances in targeting ferroptosis as a therapeutic strategy, analyze the challenges in clinical translation, and highlight future directions to inform the development of precise OA treatments.